Perceus: Garbage Free Reference Counting with Reuse (Extended version) - Reinking*, Alex; Xie*, Ningning; de Moura, Leonardo; Leijen, Daan (Microsoft, 2020)
We introduce Perceus, an algorithm for precise reference counting with reuse and specialization. Starting from a functional core language with explicit control-flow, Perceus emits precise reference counting instructions such that programs are _garbage free_, where only live references are retained. This enables further optimizations, like reuse analysis that allows for guaranteed in-place updates at runtime. This in turn enables a novel programming paradigm that we call _functional but in-place_ (FBIP). Much like tail-call optimization enables writing loops with regular function calls, reuse analysis enables writing in-place mutating algorithms in a purely functional way. We give a novel formalization of reference counting in a linear resource calculus, and prove that Perceus is sound and garbage free. We show evidence that Perceus, as implemented in Koka, has good performance and is competitive with other state-of-the-art memory collectors.
(*) The first two authors contributed equally to this work. v4, 2021-06-07. Extended version of the PLDI'21 paper.